Analisis Kepercayaan Diri Anak Usia Dini Melalui Kegiatan Ekstrakurikuler Bernyanyi Lagu Daerah di TK Dukuh Ii Sukoharjo - Ira Irmawati; Junita Dwi Wardhani (Syntax Literate, 2023)
The extracurricular activity of singing folk songs at TK DUKUH II Sukoharjo is an internal part of the learning process that emphasizes children's needs, which aims to increase the self-confidence of early childhood through extracurricular activities singing folk songs at TK Dukuh II Sukoharjo. The subjects of this study were 15 children in group A TK DUKUH II, consisting of 7 girls and 8 boys. This type of research is qualitative, research will be carried out in August 2022. Data collection techniques are carried out by observation, interviews and documentation in the hope that the resulting data is valid, subjective and authentic. Based on the results of the study, it showed that there was an increase in children's self-confidence between before and after giving treatment in TK DUKUH II Sukoharjo. This is evidenced by an increase in self-confidence which can be seen in children who are confident in themselves. It can be seen from the pre-test results of 17.0, while the post-test results of 22.3 can increase by 5.3 percentage to 1.31%. The responsible indicator is the pre-test result of 12.1, while the post-test result is 16.5 which can increase to 4.4. Percentage 1.36%. The objective indicator of the pre test results is 17.8 while the post test results are 21.9 which can increase to 4.1. Percentage 1.23%. The indicator has a happy feeling with the pre-test results of 17.6 while the post-test results are 23.8 which can increase to 6.2. percentage 1.36%. The overall results of the study from the pre-test score of 64.5 and the results of the post-test score of 84.5, it can be concluded that singing extracurricular activities can increase children's self-confidence in TK DUKUH II Sukoharjo. Confidence can be developed by using the singing method through extracurricular activities.